Effects of muscle protein denaturation and water distribution on the quality of false abalone (Volutharpa ampullacea perryi) during wet heating. (3rd December 2018) - He, Shudong; Sun, Xianbao; Du, Ming; Chen, Hui; Tan, Mingqian; Sun, Hanju; Zhu, Beiwei
Abstract: The effects of wet heating at 95–100 °C on the degree of myosin and actin denaturation in false abalone ( Volutharpa ampullacea perryi ) were predicted by a heat transfer model. The contributions of water mobility and tenderness to sensory acceptability were assessed after 5, 10, 15, 30, and 60 min heating treatments. 3D finite element heat transfer analysis and reaction kinetics demonstrated that the muscle proteins were completely denatured in 60–80 s during wet heating. In the low field 1 H nuclear magnetic resonance (LF‐NMR) and magnetic resonance imaging (MRI) analyses, the content of immobilized water was reduced with extended cooking time, and the shear force also decreased. Sensory acceptability was reduced with the increase of cooking time. Partial least squares (PLS) analysis indicated a high correlation among immobilized water, color, taste, and sensory acceptability. Our results may help in understanding the mechanisms of quality assessment and control during seafood cooking. Practical applications: False abalone ( Volutharpa ampullacea perryi ) has been widely consumed as it can provide a high quality of nutrition with a relatively inexpensive cost. Wet heating is the most conventional processing procedure, then the effects of heating on the sensory and textual properties of false abalone meat should be carefully controlled. Since most researches are concerning the changes of collagen, the present study provided quantitative characterizations of muscle protein denaturation and water distribution on the quality of false abalone using 3D finite element heat transfer analysis, LF‐NMR, MRI techniques, and PLS analysis. The results would be useful to simulate actin and myosin denaturation as well as the protons distribution under different thermal schedules of food cooking, and they could be applied for the food quality control in the industry.